Serum vitamin A and prostate cancer. - Ellison, Lawrence Fredric. (University of Ottawa (Canada), 1997)
Prostate cancer is a leading cancer in terms of both incidence and mortality in Canada and promises to become an increasing concern in the future. Despite its relative importance, few risk factors for prostate cancer have been identified. While a large number of dietary studies have examined the relationship between vitamin A and prostate cancer, studies using serum vitamin A levels are rare. A population-based retrospective cohort study was conducted. Serum vitamin A levels were measured as part of the Nutrition Canada Survey (1970-1972). Study participants (3,014) were men 35 years of age or older at time of interview for whom a serum vitamin A level was recorded. Prostate cancer cases were identified through record linkage of the survey cohort to the Canadian Cancer Registry (1971-1986). An age-adjusted Poisson regression analysis was then conducted. One hundred cases of prostate cancer were analyzed. Men with serum vitamin A levels in the highest quartile were found to be at twice the risk of developing prostate cancer as those whose levels were in the lowest quartile. For men 80 years or older, the observed relative risk exceeded three. This study suggests that serum vitamin A levels in men are positively associated with their risk of developing prostate cancer. This effect appears to be greatest among men 80 or more years of age. These findings should be interpreted with caution as this is the first study of appreciable size to report such an association and it remains possible that the results reflect, at least partially, the confounding effect of some unknown risk factor(s). Further research is needed to clarify the role of serum vitamin A in prostate cancer etiology. (Abstract shortened by UMI.)
Keywords: Biology, Biostatistics.